Rhizoma Atractylodis Macrocephalae-Assessing the influence of herbal processing methods and improved effects on functional dyspepsia - Song-Hong Yang; Jing Zhu; Wen-Ting Wu; Jun-Mao Li; Heng-Li Tong; Yi Huang; Qian-Feng Gong; Fei-Peng Gong; Fei-Peng Gong; Ling-Yun Zhong (Frontiers Media S.A., 2023)
Background: The unique pharmaceutical methods for the processing of botanical drugs according to the theory of traditional Chinese medicine (TCM) affect clinical syndrome differentiation and treatment. The objective of this study was to comprehensively elucidate the principles and mechanisms of an herbal processing method by investigating the alterations in the metabolites of Rhizoma Atractylodis Macrocephalae (AMR) processed by Aurantii Fructus Immaturus (AFI) decoction and to determine how these changes enhance the efficacy of aqueous extracts in treating functional dyspepsia (FD).Methods: A qualitative analysis of AMR before and after processing was conducted using UPLC-Q-TOF-MS/MS, and HPLC was employed for quantitative analysis. A predictive analysis was then conducted using a network analysis strategy to establish a botanical drug-metabolite-target-disease (BMTD) network and a protein-protein interaction (PPI) network, and the predictions were validated using an FD rat model.Results: A total of 127 metabolites were identified in the processed AMR (PAMR), and substantial changes were observed in 8 metabolites of PAMR after processing, as revealed by the quantitative analysis. The enhanced aqueous extracts of processed AMR (PAMR) demonstrate improved efficacy in treating FD, which indicates that this processing method enhances the anti-inflammatory properties and promotes gastric motility by modulating DRD2, SCF, and c-kit. However, this enhancement comes at the cost of attenuating the regulation of motilin (MTL), gastrin (GAS), acetylcholine (Ach), and acetylcholinesterase (AchE).Conclusion: Through this series of investigations, we aimed to unravel the factors influencing the efficacy of this herbal formulation in improving FD in clinical settings.